Reactions And Syntheses: In The Organic Chemistry Laboratory - Tietze,lf (New Jersey Wiley Vch, 2007)
Presenting a broad spectrum of modern total synthesis of natural products, pharmaceuticals, heterocycles, C-C bonding and biochemical reactions, this practical textbook readily guides readers to the necessary information. A list of keywords in each chapter and numerous tables summarize the contents, resulting in an excellent overview. Written with graduates in organic chemistry in mind, this is equally valuable for students and lecturers in chemistry, organic chemists, as well as lab technicians and chemists in industry.
Keywords: Chemistry